A Review on Need of Effective Construction Management for Box Girder Segment Erection Techniques by Under Slung (Journal of Advances and Scholarly Researches in Allied Education, 2024)
India is creating nation due to which foundation development massively expanding day by day. As result of advancement keen arrangement required for cites infrastructural development, all of which require to be coordinates with open transport. Different inquires about and improvement are held by analysts to discover financial and time sparing technic of developments. Precast concrete is one of those investigates. The support of precast strategy in development has expanded around the world within the final few decades. This strategy of superstructure casting in urban ventures proposal numerous points of interest like diminished costs, decreased development time, decreased natural impacts, and diminished support of activity. The beneath thrown strategy for propelling box support sections stands as an inventive and effective procedure in advanced bridge development. This strategy includes suspending pre-cast box support sections from transitory underpins underneath the completed parcels of the bridge and incrementally advancing these sections to make the superstructure. The ponder will investigates the complexities and points of interest of this procedure, centering on its execution .To study the part of the transitory pre-stressing framework within the cantilever gathering prepare of the precast section box support bridge, . It is additionally critical the amid the development stage of appropriate usage of administration framework to realize the security quality and opportune completion of ventures, In this paper the need of need of effective construction management is analyzed also the effective construction management is helpful for box segment erection techniques under slag will review from various research papers and literature